Associations between student organization involvement and college student mental health in the United States - Brandy Reeves-Doyle; Olutosin Sanyaolu; Karly Scott-Hillis Geller (Frontiers in Education, 2026)
Introduction The mental health of college students is a growing concern. Loneliness, belonging, and psychological distress are associated with stress, anxiety, and depression among college students. Student organization involvement is positively associated with student mental health, including lower depression. Therefore, it is worthwhile to explore the relationship between mental health and student organization involvement. This study examines the associations between student organization involvement, loneliness, belonging, and psychological distress among college students in the United States using the National College Health Assessment for secondary data analysis. Method Over 78,000 students from 125 institutions participated in the Spring 2023 NCHA. Most respondents were women (65.2%), straight (71.0%), cisgender (96.5%), and White (60.8%). Results A majority of participants reported feeling a sense of belonging (88.3%), just over half reported feeling lonely (50.8%), and most were negative for psychological distress (78.8%). Most participants were not involved in any student organizations (52.4%). Belonging increased with greater student organization participation and plateaued at higher levels. Loneliness decreased modestly across participation levels. Psychological distress showed a curvilinear pattern, with lower distress at low to moderate involvement and slight increases at the highest levels. Conclusion Recommendations for institutions of higher education are presented to help address student belonging, loneliness, and psychological distress.